Безпека людини в соціальних мережах - Овсієнко, В. С. (ХНУРЕ, 2019)
Nowadays, social networks are among the most visited resources in the global Internet. We live in them and rarely think about the dangers that may overtake us. Blackmail, provocation, robbery, manipulation are all consequences of careless use of social networks. Therefore, we need to know and understand how to protect ourselves while being on the Internet.